O comportamento dos recursos financeiros da Universidade Aberta do Brasil : um olhar para o caso da UFSCar entre 2006 E 2015 - Onody, Vanessa da Silva Mariotto (2017)
In face of the changes in the financing parameters of the Open University of Brazil System (UAB) over the course of ten years of its implementation, we established a diagnosis along with the UAB System in the Federal University of São Carlos (UFSCar) – which is composed of five undergraduate courses, two specialization courses and improvement courses in the Distance Education modality – comparing the percentage of resources for the financing of UAB-UFSCar and the percentages of resources destined to the UAB System and the total resource for the same period, destined to the Ministry of Education (MEC) for Higher Education. The objective is to indicate to what extent, in the last 10 years, the resources destined to UAB-UFSCar are proportional to the resources received to finance the UAB and the MEC, making it possible to minimize gaps and to promote a greater vision for the use and planning of the resources destined to Distant Education. For this purpose, data collection was done from information available on government websites and official documents. Subsequently statistical tests were applied to compare the volume and progress of values of the institutions. A change in the volume of resources allocated to UAB-UFSCar in relation to the UAB System and to MEC was noted in the analyzed period, a downward trend was identified over the last two years and the same drop was presented in the amount of MEC's investment resources for the UAB System since the year 2012.